2015
DOI: 10.1038/ejhg.2015.182
|View full text |Cite
|
Sign up to set email alerts
|

Defining the role of the CGGBP1 protein in FMR1 gene expression

Abstract: Fragile X syndrome is the most common heritable form of intellectual disability and is caused by the expansion over 200 repeats and subsequent methylation of the CGG triplets at the 5′ UTR of the FMR1 gene, leading to its silencing. The epigenetic and molecular mechanisms responsible for FMR1 gene silencing are not fully clarified. To identify structure-specific proteins that could recruit components of the silencing machinery we investigated the role of CGGBP1 in FMR1 gene transcription. CGGBP1 is a highly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…CGGBP1 is a 20kDa protein with a nuclear localization signal and a predicted C2H2-type Zn finger DNA-binding domain (Müller-Hartmann et al, 2000;Singh and Westermark, 2015). Electrophoretic mobility shift assays with CGG-repeat containing oligonucleotides confirmed strong affinity to CGG-repeat sequences in vitro (Deissler et al, 1996;Müller-Hartmann et al, 2000), which has also been verified in vivo at selected loci, such as the CGG repeats in the 5' UTR of the FMR1 gene (Goracci et al, 2016). Overexpression of CGGBP1 promotes the binding onto the 5' UTR of the FMR1 gene leading to transcriptional repression (Müller-Hartmann et al, 2000), suggesting that an excess of CGGBP1-bound repeats may have a dominant negative effect on transcription elongation.…”
Section: Introductionmentioning
confidence: 84%
“…CGGBP1 is a 20kDa protein with a nuclear localization signal and a predicted C2H2-type Zn finger DNA-binding domain (Müller-Hartmann et al, 2000;Singh and Westermark, 2015). Electrophoretic mobility shift assays with CGG-repeat containing oligonucleotides confirmed strong affinity to CGG-repeat sequences in vitro (Deissler et al, 1996;Müller-Hartmann et al, 2000), which has also been verified in vivo at selected loci, such as the CGG repeats in the 5' UTR of the FMR1 gene (Goracci et al, 2016). Overexpression of CGGBP1 promotes the binding onto the 5' UTR of the FMR1 gene leading to transcriptional repression (Müller-Hartmann et al, 2000), suggesting that an excess of CGGBP1-bound repeats may have a dominant negative effect on transcription elongation.…”
Section: Introductionmentioning
confidence: 84%
“…Another interesting candidate protein is the CGG-binding protein 1, CGGBP1 [ 43 ], which specifically binds unmethylated CGG repeats in a length-dependent manner [ 43 ]. Though its depletion does not change FMR1 transcription levels [ 44 ], its overexpression could be associated with an increased binding to longer CGG repeat tracts that may guide local H3K9 methylation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, like CTCF, CGGBP1 itself is a cytosine methylation-sensitive DNA-binding protein [ 20 25 ]. However, there is evidence that CGGBP1 binding to the target sequences prevents cytosine methylation from taking place [ 25 , 26 ]. WGBS experiments have shown that CGGBP1 depletion leads to genome-wide disturbances in cytosine methylation [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%